Effectiveness of Interactive E-Content Module in Enhancing Students’ Achievement in Mathematics - B. Prabakaran AR.Saravanakumar (International Journal of Control and Automation, 2020)
The objectives of the study are to find out the effectiveness between the interactive e-Content module of teaching and chalk and talk method of teaching in learning mathematics among high school students. The investigator used the pre-and-post-test of two equivalent groups design in this study. The purposive sampling technique which was adopted by selecting a sample of 20 Ninth standard students of each group was assigned to the conventional and modern method of teaching. An e-content module and a teacher made achievement test was developed by the researcher under the guidance of research supervisor based on the Mathematics subject portion as set theory including drawing skills of Venn diagram. Fmax test, independent t-test, ANCOVA test, ηp2 test, R2 test, ω2 test, r2 test, Effect Size and Gain Ratio test are used for statistical analysis and interpretation for achievement scores (data) and the results are discussed in this paper along with the findings and recommendations.